2010
DOI: 10.3109/00365548.2010.509332
|View full text |Cite
|
Sign up to set email alerts
|

Skin and soft tissue infections caused by Staphylococcus lugdunensis: Report of 20 cases

Abstract: Staphylococcus lugdunensis is an unusually virulent coagulase-negative Staphylococcus (CoNS). The aim of the present study was to investigate the clinical and microbiological characteristics of 20 cases of skin and soft tissue infections (SSTIs) due to S. lugdunensis that occurred in our area. The frequency of SSTIs due to this organism was 0.42%. The infection was secondary to trauma, surgery or skin disease in 15 patients (75%). Abscesses (7 cases), surgical wound infections (6 cases) and cellulitis (3 cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 28 publications
2
30
1
3
Order By: Relevance
“…Such associations of S. lugdunensis with severe infections were previously reported in various patient cases and series, including specimens from various origins, i.e. endocarditis, skin and soft tissue infections, arthritis, prosthetic joint infections, sepsis without identified gateway, pseudo-toxic shock syndrome, necrotizing sinusitis, and brain abscesses (30)(31)(32)(33)(34)(35). S. lugdunensis is the second cause of endocarditis due to CoNS, with a poor prognosis in 40% of cases (36).…”
Section: Discussionmentioning
confidence: 59%
“…Such associations of S. lugdunensis with severe infections were previously reported in various patient cases and series, including specimens from various origins, i.e. endocarditis, skin and soft tissue infections, arthritis, prosthetic joint infections, sepsis without identified gateway, pseudo-toxic shock syndrome, necrotizing sinusitis, and brain abscesses (30)(31)(32)(33)(34)(35). S. lugdunensis is the second cause of endocarditis due to CoNS, with a poor prognosis in 40% of cases (36).…”
Section: Discussionmentioning
confidence: 59%
“…The duration of antibiotic treatment ranged from 5 to 21 days, with all isolates susceptible to most of the antibiotics tested. 6 Although this study demonstrated that S. lugdunensis is penicillin sensitive, a 3-year retrospective study demonstrated that 80% of isolates (> 50% from skin) were penicillin resistant (80%). 8 This potential variability in the antibiotic resistance profile of S. lugdunensis is far greater than historical estimates and demonstrates the need for testing antibiotic sensitivities when coagulase-negative staphylococci are encountered.…”
Section: Discussionmentioning
confidence: 72%
“…6 The frequency of skin infections due to S. lugdunensis was calculated to be 0.42%, with infection found to be secondary to trauma, surgery or skin disease in 15 of the 20 patients (75%). Of the 20 cases, abscesses (seven cases), surgical wound infections (six cases) and cellulitis (three cases) were the most common clinical presentations.…”
Section: Discussionmentioning
confidence: 99%
“…lugdunensis has been reported as an agent of endovascular infection, particularly in patients with inguinal skin breaks (vasectomy or cardiac catheterization via the femoral route [6,8]) and as a cause of pelvic girdle abscesses (2), highlighting that the predominant ecological niche of the organism is likely to be the groin. S. lugdunensis has also been reported as a cause of skin and soft tissue infections, particularly involving the breast, abdomen, and lower limbs (1,2,4), and has been identified as an agent of prosthetic joint infection (10). In keeping with these reports, studies that have screened healthy persons for carriage have confirmed identification from skin of the abdomen, groin, and lower extremities (3,12).…”
Section: S Lugdunensis Is a Coagulase-negativementioning
confidence: 83%
“…However, based on the production of bound coagulase (5), S. lugdunensis can also easily be misidentified in the laboratory as S. aureus (8), as was initially the case in this instance. Because it shares certain virulence characteristics with S. aureus, S. lugdunensis is now well recognized as a potential cause of invasive and destructive infections that can mimic S. aureus disease (1,4,7,10,14).…”
Section: S Lugdunensis Is a Coagulase-negativementioning
confidence: 99%